(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The purpose of this research is to affirm the view that the lack of authentic written and archaeological testimonies of Old Slavic mythology can be compensated by a more intensive inclusion of folk tradition. Тhe application of the folklore-ethnographic method can fulfill many gaps in the complete representation of the ancient Slavic faith, the apostroffe in this research is placed on the ethnographic materials from Cepenkov’s folk collection (notes of folk beliefs and superstitions). In this mythological reconstruction, other folklore materials from Cepenkov’s records are taken into account, which contain remnants of the former mythological beliefs, which over time are filled with new symbolic content and thus are "resemanticized". By checking certain mythological beliefs from Old Slavic mythology on selected folklore material, the continuity of certain mythical representations was proved. Hence the conclusion that some of the Old Slavic mythological beliefs (potentially from the Old Slavic myths!) have survived in the folk tradition, and the reconstruction of the Old Slavic mythical heritage can be intensified by applying the folklore-ethnographic method. Keywords: Folklore-ethnographic method, Slavic mythology, ethno-astronomy, folk beliefs and legends, astronomical-meteorological codes.